Effects of geographic origin and temperature on survival, development, and emergence of the managed pollinator Osmia lignaria - Scalici, Morgan B.; McCabe, Lindsie M.; Alston, Diane G.; Pitts-Singer, Theresa L. (Frontiers in Ecology and Evolution, 2023)
The blue orchard bee, Osmia lignaria, is a widespread North American native pollinator that can be employed for commercial fruit and nut crop production. The largest supplies of these bees are collected from the wildlands of Utah and Washington, USA. How O. lignaria from different geographic regions respond to current recommended management practices or translocation to novel environments is not fully understood. Utah- and Washington-originated O. lignaria were reared in laboratory incubators under two thermal regimens: 1) constant temperatures used to manage bees through immature development, adult winter dormancy, and for spring emergence, and 2) hourly fluctuating temperatures programmed to mimic the natural daily (24 h) thermal cycles of the nearest cherry orchard growing region through their life cycles. In comparison to rearing bees at natural temperatures, we found that rearing bees at a constant temperature increased survival and shortened egg–adult development periods. Washington bees were more adversely affected by the consistent warm rearing temperatures than were Utah bees, possibly due to adaptations to Washington’s relatively moderate climate. At orchard temperatures, Utah bees suffered high prepupal and pupal mortality, while Washington bees suffered high pupal and adult mortality. These late life stages coincided with the hottest maximum temperatures in their representative thermal regimens. Adult females from both states naturally emerged in synchrony with local bloom time, but their emergence period overall was prolonged compared to bees in the constant temperature regimen that were induced to emerge at orchard bloom times. Our data support that bees originating from cool montane habitats of different U.S. states suffer from the warmer climatic conditions at lower altitudes of their respective crop-growing regions. A better understanding of optimal management temperatures for O. lignaria from different geographic regions and the effect of bee origin and temperature on survival and development timing is needed for best managing these pollinators when they are translocated or when climate change results in increased temperatures during bee development periods.